PENANAMAN KESADARAN SEJARAH SATU RUMPUN SEBAGAI UPAYA MENINGKATKAN HUBUNGAN BILATERAL INDONESIA-MALAYSIA - Nur Aeni Marta (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2024)
Abstract This community service program was initiated to address the issue of negative stereotypes and prejudices between Indonesia and Malaysia, which often hinder bilateral relations, especially among the younger generation. The problem arises from a lack of understanding of shared history and cultural roots, making it necessary to raise awareness of these commonalities. The program aims to strengthen historical and cultural awareness through educational activities. Workshops and joint seminars were held, involving students from both countries in discussions focused on shared history and cultural heritage. The International Community Service Seminar, titled